Leadership and employee engagement in the New Zealand dairy farming industry - is there a link with milk production performance? : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Manawatu, New Zealand - Rolfe, Christina (Massey University, 2017)
This study sought to investigate which leadership styles were more effective at increasing employee engagement and/or overall milk production performance in the context of the New Zealand (NZ) dairy farming industry. This study also sought to investigate whether psychological needs satisfaction mediated the relationships between leadership styles and employee engagement. A cross-sectional self-report survey was used to collect data. Results indicated that transformational-contingent reward leadership was related to higher levels of employee engagement, while passive-avoidant leadership, management by exception active, and destructive leadership styles were all negatively related to employee engagement. Satisfaction of the need for autonomy was found to fully mediate the relationship between transformational-contingent reward leadership and employee engagement, between passive-avoidant leadership and employee engagement, and also between destructive leadership and employee engagement. None of the independent variables were found to have significant relationships with overall milk production performance. Theoretical and practical implications for effective leadership styles are discussed along with recommendations for future research.
Keywords: Dairy farming; Personnel management; Employee motivation; Employees; Attitudes; Milk yield; New Zealand